The Influence of the Coaching Method on Teacher Work Motivation: A Quantitative Study at Private Junior High School in Lasem District Rembang Regency - Pujoko, Pujoko; Rasiman, Rasiman; Supandi, Supandi (FKIP - Universitas Riau, 2025)
Teacher work motivation is a crucial determinant of educational quality, as motivated teachers are more likely to demonstrate creativity, commitment, and consistent performance in the classroom. In many under-resourced private junior high schools, including those in Lasem District, Indonesia, motivation remains a challenge due to limited professional development opportunities and inconsistent supervisory practices. This study aims to examine the influence of the coaching method on teachers’ work motivation in private junior high schools in Lasem District. Using a quantitative approach with an explanatory research design, the study involved 62 teachers selected through total sampling. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed through simple linear regression. The findings reveal a significant positive relationship between the coaching method and teachers’ work motivation, with coaching contributing meaningfully to variations in motivation. Teachers who experienced reflective and collaborative coaching reported greater confidence, professional commitment, and enthusiasm in their teaching roles. It is concluded that structured coaching is an effective strategy for enhancing teacher motivation, aligning with Self-Determination Theory and Herzberg’s Two-Factor Theory, and holds potential as a strategic intervention to improve teacher performance and educational quality in resource-limited contexts.